Immunomorphological Changes in Cervical Cancer and Their Clinical Significance (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cervical cancer (CRC) is a dangerous tumor that ranks second among women's oncological diseases and is characterized by high mortality. According to the World Health Organization (WHO), approximately 600 thousand new cases and about 300 thousand deaths are recorded in the world every year. This disease remains a serious problem for women's health in Uzbekistan as well.